Modern approaches to treating drug-resistant epilepsy - ketogenic diet, innovative drugs and neurosurgery - Rzenno, Robert; Brzozowska, Monika; Wardal, Wiktoria; Furlepa, Natalia; Wojciechowska, Karolina; Matuszewska, Marcelina; Wicha, Katarzyna; Sidz, Natalia; Tomaszewska, Magdalena; Jedlikowska, Wiktoria (Quality in Sport, 2025)
Introduction and objective Drug-resistant epilepsy (DRE) is a type of epilepsy where seizures persist despite treatment with multiple antiepileptic drugs being implemented. This condition severely affects the quality of life of those impacted, often leading to difficulties in daily functioning and associated mental health issues such as anxiety and depression. The goal of this study is to investigate the mechanisms behind drug-resistant epilepsy and review the current approaches to its diagnosis and treatment. Review methods A thorough literature review was carried out using the PubMed database to explore studies focused on drug-resistant epilepsy. Key search terms included "drug-resistant epilepsy", “DRE”,. The review concentrated on the latest research examining the pathophysiology, diagnostic tools, and treatment strategies for individuals with DRE. Description of the state of knowledge Drug-resistant epilepsy is often associated with disruptions in neuronal activity, changes in protein expression, and imbalances in neurotransmitters. These factors contribute to the lack of response to standard antiepileptic medications. Diagnostic procedures currently involve electroencephalography (EEG) to assess brain activity, along with advanced imaging techniques like MRI and CT scans to detect any structural abnormalities. Available treatments encompass a range of drug therapies, surgical options, neurostimulation, and dietary interventions. Conclusions The review highlights that, despite notable progress in understanding drug-resistant epilepsy, there are still significant challenges in developing effective treatments. Continued research into the molecular mechanisms and advancements in diagnostic tools are essential for improving the management of this condition and creating more targeted treatment options.